2018
DOI: 10.2486/indhealth.2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Altered immune responses in broiler chicken husbandry workers and their association with endotoxin exposure

Abstract: Exposure to bioaerosols in indoor animal farms associates with respiratory illnesses, but little is known about the immune modulation to chicken farmers. This study aimed to compare the general immunity of chicken farmers with those of control subjects with non-agricultural jobs. Blood taken from the farmers and controls was subjected to plasma IgE and IgG subclass measurements. Isolated peripheral blood mononuclear cells (PBMC) were stimulated and cytokine production was measured. Indoor total and respirable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…After stimulation, a greater increase was observed in the nonfarmer group. 14 The results of this study are only partially consistent with ours; it seems that the main problem is the small size of study groups.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…After stimulation, a greater increase was observed in the nonfarmer group. 14 The results of this study are only partially consistent with ours; it seems that the main problem is the small size of study groups.…”
Section: Discussionsupporting
confidence: 62%
“…Chicken breeders had a threefold higher serum IgE level, but statistical significance was not reached. 14 Farming lifestyle in the first year of life was associated with decreased serum IgE concentration. Other study assessing total IgE levels in the serum of Danish agricultural school students showed significantly lower levels of this immunoglobulin in those who spent their childhood on a farm, both compared to farm residents growing up out of farm and those from the countryside who never lived on a farm.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is an essential organ for nutrient absorption and a fundamental protective barrier against incursions of bacteria, pathogens, and toxins; therefore, maintaining intestinal homeostasis is of great importance [ 29 ]. There is increasing evidence that suggests LPS, a common toxin in the poultry industry [ 30 ], leads to loss of body weight [ 31 ], intestinal epithelium injury [ 32 ], increased intestinal permeability [ 33 , 34 ], and microflora dysbiosis [ 35 ]. Bioactive agents with various biological benefits [ 36 ], such as FA, may represent an interesting solution.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of increasingly modern poultry farming systems, its presence in farm buildings is still associated with significant human pulmonary exposure to dust-derived microorganisms and their by-products. In the present study, particulate aerosol concentrations (understood here as inhaleable fraction of dust) determined in poultry house, did not differ in their levels from the concentrations determined in this type of work environment by other researchers (proper value ranges are given in parentheses) in: Spain (0.03-15.2 mg/m 3 ) [6,15], Switzerland (0.42-21.75 mg/m 3 ) [45], The Netherlands (4-4.4 mg/m 3 ) [46], Croatia (1.8-4.8 mg/m 3 ) [47], Sweden (1.76-5.17 mg/m 3 ) [48], USA (0.03-5.58 mg/m 3 ) [49][50][51][52], China (0.17-9.61 mg/m 3 ) [53], Korea (0.53-31.5 mg/m 3 ) [54][55][56], Pakistan (0.66-1.56 mg/m 3 ) [13], Iran (2-5.4 mg/m 3 ) [57], Saudi Arabia (2.11-18.11 mg/m 3 ) [58], Egypt (0.63-3.13 mg/ m 3 ) [43], South Africa (1.16-57.52 mg/m 3 ) [44], and were almost on the same level as in an earlier study performed by the authors of the current study in poultry houses in southern Poland (0.03-4.51 mg/m 3 ) [58]. However, some measurements carried out in the USA [59] and China [60] revealed much higher inhalable poultry dust levels in chicken farms, reaching 92.4 mg/m 3 and 230 mg/m 3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The hitherto obtained endotoxin concentrations in the poultry farm environment present a rather consistent picture of such pollution which in individual countries on different continents reaches the following values (adjusted from EU/ m 3 to ng/m 3 using 10 EU equal to 1 ng as conversion factor): in Switzerland (18.99-1,634.8 ng/m 3 ) [45], United Kingdom (0.02-76.2 ng/m 3 ) [67,68], The Netherlands (45.22-469.3 ng/m 3 ) [46,67], Denmark (116.6-139.7 ng/m 3 ) [67], Sweden (10-1,003 ng/m 3 ) [48,66], France (3.5-315.6 ng/m 3 ) [64], Germany (1.98-6,434.7 ng/m 3 ) [67,69], Korea (0.16-251 ng/m 3 ) [54][55][56]70], Iran (5.4-23.6 ng/m 3 ) [57], and the USA (13.5-1,360 ng/m 3 ) [49,51,67]. Endotoxin concentrations measured in earlier research by the authors of this study, performed in poultry houses in southern Poland, were at much higher levels (0.04-8,364 ng/m 3 ) [58] than those noted in the current study.…”
Section: Discussionmentioning
confidence: 99%